Legal Review of the Prohibition on Ownership of Agricultural Land Outside the Sub-district in the Division of Gono Gini Assets - Eko Muljono, Bambang; Suhaili, Achmad; Suisno; Qudhoifah, Ahmad (Jurnal Independent, 2026)
ownership by people outside the sub-district area as a result of the distribution of gono-gini property. The main problem studied is how the synchronization and legal implications between the principle of division of joint property in marriage (gono-gini) and the provisions of laws and regulations in the field of land that limit the ownership of agricultural land based on geographical domicile. The research method used is normative legal research with a statutory approach and a conceptual approach. Primary legal materials include the Basic Agrarian Law, the Regulation of the Minister of Agrarian and Spatial Planning/Head of BPN related to the limitation of agricultural land ownership, as well as the provisions of inheritance and marriage law. Secondary legal materials are analyzed qualitatively. The results of the study show that the prohibition of agricultural land ownership by people outside the sub-district area creates a conflict of norms when applied to the division of gono-gini property, especially if one or both spouses no longer reside in the sub-district where the land is located. There is a legal vacuum regarding the mechanism for the transfer of agricultural land rights due to gono-gini that exceeds the boundaries of the sub-district. This study recommends the need for extensive interpretation or regulatory changes to provide exceptions to the prohibition in the context of the distribution of common property, as well as the need for legal certainty for parties who acquire land through gono-gini but are outside the sub-district area.